Microsoft Windows Workflow Foundation step by step - Scribner, Kenn (Step by step (Redmond, Wash.), 2007)
Get hands-on guidance for using Microsoft Windows Workflow Foundation to create process-managed applications for Microsoft Windows--one step at a time. Understanding Windows Workflow Foundation is essential for every developer who works with multiple applications and services that must exchange data or results. Windows Workflow Foundation defines a process flow amongst people, applications, and services--mapping dependencies and sequences to allow automation of tasks across previously stand-alone programs. With STEP BY STEP, you work at your own pace through hands-on, learn-by-doing exercises to understand the core capabilities and fundamental techniques for working with Windows Workflow Foundation. New-to-topic developers can take a sequential approach to understanding workflows and learning how to create Windows Workflow Foundation-enabled applications and services. This book includes practice exercises and code samples to help developers accelerate their productivity.